2024
DOI: 10.1002/smll.202306653
|View full text |Cite
|
Sign up to set email alerts
|

Structural Effects of 3D Inkjet‐Printed Ni(O)‐YSZ Pillared Electrodes on Performances of Solid Oxide Electrochemical Reactors

Inyoung Jang,
Anna Hankin,
Zheng Xie
et al.

Abstract: Increasing densities of reaction sites for gaseous reactants in solid oxide electrochemical reactors (SOERs), is a key strategy for achieving enhanced performance in either fuel cell or electrolysis modes. Fabrication of 3D structured components in SOERs can enhance those densities of reaction sites, which is achieved by 3D inkjet printing with high reproducibility, having developed inks with appropriate properties. First, the effects of pillar geometries on SOER performances are predicted through numerical si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In subsequent research, the team further advanced inkjet printing technology for pillar formation, optimising the fabrication processes for YSZ pillars and YSZ-NiO pillars with extended lengths [101].…”
Section: D Printing For As-socsmentioning
confidence: 99%
See 1 more Smart Citation
“…In subsequent research, the team further advanced inkjet printing technology for pillar formation, optimising the fabrication processes for YSZ pillars and YSZ-NiO pillars with extended lengths [101].…”
Section: D Printing For As-socsmentioning
confidence: 99%
“…In this study, simulations have demonstrated that when YSZ and Ni-YSZ pillars are optimised, the performance of fuel cells could potentially be enhanced by factors of 2.85 and 4.9, respectively (figure 20(e)). Experimental validation of these results has been attempted through inkjet printing [101].…”
Section: Toward the 3d Socs Modellingmentioning
confidence: 99%